The character in Burhan Shawi’s mazes (Journal of the College of Basic Education, 2024)
The research included the narrative personality in the labyrinths of Burhan Shaoui, due to its significant clear role in the labyrinths. The study came within this technique that distinguished by its methods of fictional characters' presentation, and it revealed to us how the characters are presented to themselves or others through their actions or behaviors. The rates of characters' presentation varied and the character that informs about another has dominated over that which tells about itself (its condition), also the variable characters (round) have dominated clearly and significantly over the developing characters (flat).